1992
DOI: 10.1128/iai.60.3.998-1007.1992
|View full text |Cite
|
Sign up to set email alerts
|

Passive protective effect of chicken egg yolk immunoglobulins against experimental enterotoxigenic Escherichia coli infection in neonatal piglets

Abstract: Passive protection of neonatal piglets against fatal enteric colibacillosis was achieved with powder preparations of specific antibodies against K88, K99, and 987P fimbrial adhesins of enterotoxigenic Escherichia coil. The antibody powders were obtained by spray drying the water-soluble protein fraction of egg yolks from immunized hens after the lipid components were precipitated with an aqueous dispersion of acrylic resins (Eudragit L3OD-55; Rohm pharma). The anti-K88,-K99, and-987P antibody preparations reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(101 citation statements)
references
References 20 publications
5
91
1
4
Order By: Relevance
“…In contrast to the current study and that reported by Quigley and Drew (2000), these calves began consuming the anti-rotavirus colostrum at birth, thereby allowing some Ig absorption. Similarly, newborn pigs were protected against E. coli challenge-induced diarrhea when orally dosed with egg yolk-based antibody solutions obtained from immunized hens (Yokoyama et al, 1992). The bovine-serum material used in the current study was not tested for titers against BCV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current study and that reported by Quigley and Drew (2000), these calves began consuming the anti-rotavirus colostrum at birth, thereby allowing some Ig absorption. Similarly, newborn pigs were protected against E. coli challenge-induced diarrhea when orally dosed with egg yolk-based antibody solutions obtained from immunized hens (Yokoyama et al, 1992). The bovine-serum material used in the current study was not tested for titers against BCV.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, IgY has been used extensively for prevention and treatment of various infections in animals and humans with mixed success (Hamada & Kodama, 1996). Other potential uses of IgY in immunotherapy and immunodiagnostics has been reported by many authors (Ambrosius & Hadge, 1987;Larsson & Sjoquist, 1988;Otake et al, 1991;Yokohama et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…IgY has been orally administered to piglets and offers a potential prophylactic and therapeutic approach for controlling E. coli-induced diarrhea. Yokoyama et al (1992) showed that orally administered IgY generated against E. coli K88, K99, or 987P fimbriae was protective against infection from each of the three homologous strains of E. coli in a dose-dependent manner. E. coli K88, K99, and 987P strains adhered equally to porcine epithelial cells from the duodenum and ileum but failed to so in the presence of homologous anti-fimbrial IgY.…”
Section: Diarrhea In Pigletsmentioning
confidence: 99%